Anterior and posterior diaphragm kinesio taping for intractable hiccups after ischemic stroke: A case report. Issue 34 (August 2018) - Gallagher, Julie
Abstract: Rationale: Pathophysiologic mechanisms of the central nervous system, such as stroke, can be associated with intractable hiccups. Intractable hiccups can be associated with potentially fatal consequences, thus requiring safe management in an inpatient rehabilitation facility (IRF) setting with a multidisciplinary team approach to optimize mobility and feeding. Patient Concerns: A 49-year-old male presented to the emergency department with complaints of vomiting and dizziness. Diagnoses: Head computed tomography revealed moderate acute inferior cerebellar infarct in the territory of the posterior inferior cerebellar artery. He required a percutaneous endoscopic gastrostomy tube for feeding and developed severe intractable hiccups which he rated 7/10 on the hiccup assessment instrument (HAI) on IRF admission. Functional independence measure (FIM) score for transfers was 2 (maximum assist), walking was 1 (total assist), stairs were not attempted on IRF admit due to safety concerns, and feeding (eating) was 1 (total assist). Interventions: Anterior and posterior diaphragm kinesio taping was applied on day 6 of IRF physical therapy in an attempt to inhibit diaphragm spasm and intractable hiccups given that pharmacologic interventions had not been effective up to that point (Table 3). Outcomes: The HAI decreased from 7/10 on day 6 of IRF physical therapy to 0/10 on day 8. The taping was reapplied every 3 to 5 days. On IRF day 9, his diet was advanced to a regular consistency with extra moisture and thin liquids. On day 21, hiccup severity remained 0/10 on the HAI, while FIM score for transfers was 4 (minimal assist), walking was 4 (minimal assist), stairs was 4 (minimal assist), and feeding (eating) was 7 (independent). Lessons: Diaphragm kinesio taping is a very effective treatment at reducing hiccup severity in a patient after ischemic stroke, while at the same time reducing burden of care for caregivers per FIM score improvement and improving diet to that of regular consistency with extra moisture and thin liquids.